Pheidias Apollonius (ca. 4th century BC), unveiling the ancient Greek medico philosophical school of the island of Rhodes - Tsoucalas, Gregory (Array, 2018)
The ancient Greek medico-philosophical school of the island of Rhodes was lost in the fog of history. However, the discovery of a stone column dedicated to Pheidias unveiled somehow some parts of its tale. The Island of Rhodes became in the 4th century BC a place of significant process in philosophy and medicine. Having both an Asclepieion and a Medical School with a rich library, the Rhodian Asclepiades transmitted their knowledge to future schools. Pheidias Apollonius was a member of the School of Rhodes, who was celebrated for his practise by the city-state of Athens. His magnitude testified in a way the supremacy of the school that he originated from.